Dynamic high resolution US as primary tool in comparison to MRI in evaluation of TMJ disk anterior displacement - Ahmed Y. Ashour; Abdalwhab M.A. Zwiri; Ahmed H. Ali; Ahmed M. Mostafa; Bahaa-Eldin A. Moustafa; Husseini F. EL boraey; Alshimaa Y. Ashour; Elsayed M. Abd El-Hamid (Translational Research in Anatomy)
Background: Many adults are affected by temporo-mandibular joint dysfunction (TMD). Several imaging modalities as Magnetic resonance imaging (MRI), computed tomography (CT), and traditional radiography were used to diagnose TMD. Among these modalities, dynamic high-resolution ultrasound (US) emerges as a potential non-invasive, radiation-free method. Objective: This study aimed to compare the efficacy of US versus MRI in the assessment of TMJ displacement. Methods: This study included forty patients with a clinical diagnosis of anterior disk displacement (ADD). The TMJ was imaged bilaterally using a 1.5 T MRI using a 2-mm slice width, in the sagittal and coronal planes 1–7 days after performing US. The diagnostic accuracy of the ultrasound was evaluated for disc displacement in contrast to MRI. For US the following metrics: sensitivity, specificity, accuracy, positive predictive value, and negative predictive value were used to compare the measurements versus MRI. Results: Patients were 14 male and 26 female patients (mean age 29.36 ± 7.09 years) with a duration of ADD of 3.2 ± 1.7 months. The most common clinical indications were TMJ stiffness and discomfort (85 %), followed by limited mouth opening (75 %), and TMJ sounds (crepitus/clicking) (80 %). Most patients had mild TMJ dysfunction (44.0 ± 16.42). The MRI was better in identifying TMJ abnormalities than the US. However, no significant differences were observed. Compared to MRI, US showed superior diagnostic sensitivity, specificity, and accuracy for TMJ disc displacements. Conclusions: According to the study's findings, US can be suggested as a very precise imaging method for identifying internal TMJ abnormalities.